Adaptation of folk games to accelerated swimming training of junior schoolchildren in outdoor swimming pools or reservoirs - Olha Obrazhei (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
The goal of the research was to test the effectiveness of the introduction of adapted Ukrainian folk games into the methodology of teaching swimming to junior schoolchildren in outdoor swimming pools or reservoirs. Methodology: theoretical analysis and summary of scientific and methodological literature, pedagogical observations, testing, pedagogical experiment, methods of mathematical analysis and statistics. Results. To assess the children's swimming fitness during the research, we developed a set of swimming tests. The results showed that we were able to significantly reduce a fear of water in junior schoolchildren by 28% (p <0.001). The smallest increase in rating was obtained in the tests "underwater breath hold" and "starfish float" - 25% (p <0.05) each, "putting a face in the water" - 27% (p <0.001), and "gliding and arm movements" - 30% (p <0.01). The highest rate of improvement was found in tests that measure coordination in swimming - 35% (p <0.001) and gliding and leg movements - 36% (p <0.05). The index of schoolchildren's swimming training increased by 0.31 during the research. Conclusion. The obtained test results and index of swimming training (0.85) indicate the effectiveness of the introduction of adapted Ukrainian folk games into the methodology of teaching swimming to junior schoolchildren in outdoor swimming pools or reservoirs.